Software educativo para matemática del 3er año de bachillerato general unificado, en el colegio de bachillerato “Beatriz Cueva de Ayora”, de la ciudad de Loja, periodo 2014 -2015 - González Labanda, Jhony Efrén (2016)
The topic discussed in the work titled "EDUCATIONAL SOFTWARE FOR THE 3RD YEAR OF MATHEMATICS BACHELOR GENERAL UNIFIED SCHOOL HIGH SCHOOL IN" BEATRIZ CAVE AYORA "CITY OF LOJA, Period 2014 - 2015". Ecuador is a country that has taken important initiatives to improve the quality of education, considering the use and implementation of ICT, building new computer labs, digital whiteboards or better yet have created Educational Unit Goals; However, despite the significant efforts and investment in regard to education in Ecuador, obviously still not enough. For example you could say that the works have not yet reached all sectors, or may be the case that no knowledge of the update have on the use of new strategies, methods and teaching resources computerized by the teachers, for the use of the lecture and the board are the main elements only in certain cases, and to conduct classes. The use of educational software in the classroom has several advantages such as the use of the educational potential of computer and motivating for students in the mathematics program where students require more instructional support. To obtain data, information and results inductive, deductive, descriptive statistical method, whereby the treatment of the problem is done, the definition of guidelines for development of educational software and description of the thesis report were applied. The technique used was the survey that applied to teachers and students of the school. For the development of educational software methodology cascade comprising executing the steps of requirements analysis, software design, coding, testing, and implementation was used. The results provide evidence that students have a moderate level of knowledge about the use of the computer, which enables them to use the educational software developed; They also point out that the block algebra and geometry is the most complex study. Teachers in turn indicate that currently use traditional materials to teach their classes, and require educational resources; Thus the educational math software for high school 3rd was created and implemented in the school, through a socialization of operation and application training technique in teaching learning process; It left as a recommendation in organizing the use of the computer centers for teaching-learning process in the different subjects, at least once a week, so that the application of ICT by teachers in their pedagogical work is promoted.